PEMBENTUKAN KARAKTER CINTA TANAH AIR MELALUI KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DAN PROFIL PELAJAR RAHMATAN LIL ALAMIN - Thowilah, Toyyibatut; Hoiriyah (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2024)
Character education is education that has a form of educational activity in it that aims to form self-improvement, train and build self-image towards a better person. Strengthening character education is an effort made so that children have akhlakul karimah and can be practiced in everyday life. There are 18 character values in character education which include: religiosity, love for the country, national spirit, tolerance, honesty, discipline, hard work, independence, creativity, democracy, curiosity, respect for achievement, communicative, peace-loving, fond of reading, environmental care, social care and responsibility. Along with changes in the 21st century learning paradigm, educational institutions are required to adapt to changes and continue to innovate. One of the strengthening of the character of love for the country carried out by the Raudhatul Athfal (RA) Muslimat NU Nurud Dholam Education Unit in early childhood is through project activities to strengthen the Pancasila student profile and the rahmatan lil alamin student profile or commonly called P5 and P2RA. Based on observations at RA Muslimat NU Nurud Dholam Majungan Pamekasan, P5 and P2RA activities are a separate motivation for children to love their homeland more. This research is a type of qualitative descriptive research. Data collection in this study used selection techniques with certain considerations. The instruments used include observation, documentation and interviews. The subjects in the study were children with an age group of 5-6 years at RA Muslimat NU Nurud Dholam Majungan Pamekasan.